2020
DOI: 10.3844/ajeassp.2020.610.626
|View full text |Cite
|
Sign up to set email alerts
|

Fire Evaluation of RC Frames Strengthened with FRPs Using Finite Element Method

Abstract: Reinforced Concrete (RC) structures may confront with extreme loading conditions. Sometimes, structures are not only under extreme loading such as earthquakes but also, they may be subjected to fire. Therefore, investigation of reinforced concrete structures which are the most common ones is essential. In this study, experimental RC frame is considered to validate in ABAQUS finite element software. RC frame is subjected to both earthquake and fire loading condition to assess the seismic behavior of structure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An improved performance was seen with the BFRP. Moreover it was also found that reduced stiffness during higher temperatures can withstand the re hence a combination of steel along with BFRP can produce an improved stiffness than regular bars of steel [14]. Not only BFRP are found to be robust, FRCM-Fiber Reinforced Cementitious Matrix are found to be robust with RC frames with non-ductility [15].…”
Section: Literature Reviewmentioning
confidence: 91%
“…An improved performance was seen with the BFRP. Moreover it was also found that reduced stiffness during higher temperatures can withstand the re hence a combination of steel along with BFRP can produce an improved stiffness than regular bars of steel [14]. Not only BFRP are found to be robust, FRCM-Fiber Reinforced Cementitious Matrix are found to be robust with RC frames with non-ductility [15].…”
Section: Literature Reviewmentioning
confidence: 91%
“…Abdulghani & Jaafer [19] Steel fibers and SIFCON Salehi et al [20] Combining steel-BFRP bars and different BFRP sheet angles Mohammed et al [21] Fiber-reinforced polymers (FRPS)…”
Section: Type Of Strengtheningmentioning
confidence: 99%